2021
DOI: 10.1021/acschembio.1c00212
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic Nanoparticles Impacting B and T Lymphocyte Responses Delay Autoimmune Arthritis in K/BxN Mice

Abstract: Current treatments for unwanted antibody responses largely rely on immunosuppressive drugs compromising overall immunity. New approaches to achieve antigen-specific tolerance are desirable to avoid unwanted side effects. Several nanoparticle-based approaches that utilize different mechanisms to tolerize the B or T cell arms of the humoral immune response have shown promise for induction of antigen-specific tolerance, raising the possibility that they could work synergistically if combined. Earlier we showed th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Because Siglecs are primarily expressed on immune cells, they are recognized as attractive targets for cell-specific therapies that can enhance desired immune responses or suppress unwanted immune responses. As one strategy to suppress unwanted immune responses by B cells and mast cells, we developed Siglec tolerizing antigenic liposomes (STALs) that display both an antigen (or allergen) and glycan ligands of inhibitory Siglecs. For B cells, the antigen is recognized by a B-cell receptor (BCR) comprising membrane-bound IgM and/or IgD and a high affinity ligand of a B-cell Siglec (CD22 or Siglec-G/10). , When administered in vivo, STALs suppress activation of B cells that recognize the antigen and cause apoptosis of the B cells, resulting in tolerance to subsequent antigen challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Siglecs are primarily expressed on immune cells, they are recognized as attractive targets for cell-specific therapies that can enhance desired immune responses or suppress unwanted immune responses. As one strategy to suppress unwanted immune responses by B cells and mast cells, we developed Siglec tolerizing antigenic liposomes (STALs) that display both an antigen (or allergen) and glycan ligands of inhibitory Siglecs. For B cells, the antigen is recognized by a B-cell receptor (BCR) comprising membrane-bound IgM and/or IgD and a high affinity ligand of a B-cell Siglec (CD22 or Siglec-G/10). , When administered in vivo, STALs suppress activation of B cells that recognize the antigen and cause apoptosis of the B cells, resulting in tolerance to subsequent antigen challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Because Siglecs are primarily expressed on immune cells, they are recognized as attractive targets for cell-specific therapies that can enhance desired immune responses or suppress unwanted immune responses. As one strategy to suppress unwanted immune responses by B cells and mast cells, we developed Siglec tolerizing antigenic liposomes (STALs) that display both an antigen (or allergen) and glycan ligands of inhibitory Siglecs. For B cells, the antigen is recognized by a B-cell receptor (BCR) comprising membrane-bound IgM and/or IgD and a high affinity ligand of a B-cell Siglec (CD22 or Siglec-G/10). , When administered in vivo, STALs suppress activation of B cells that recognize the antigen and cause apoptosis of the B cells, resulting in tolerance to subsequent antigen challenge. For mast cells, the STALs display an allergen, recognized by an IgE bound to the FcεRI receptor, and a high-affinity ligand of a mast cell inhibitory Siglec such as CD33/Siglec-3 or Siglec-8. , When injected into a mouse sensitized to an anti-allergen IgE, mast cell degranulation mediated by the allergen is suppressed by recruitment of the Siglec, preventing severe systemic anaphylaxis and desensitizing the animal to subsequent allergen challenge. , …”
Section: Introductionmentioning
confidence: 99%
“…While the K/BxN mice are genetically programed to develop anti-GPI antibodies, in the studies reported here, CD22L-NP­(R)-GPI was administered prior to the onset of disease, as defined by joint swelling. However, we have previously shown that by using a two NP strategy combining CD22L liposomes (GPI-STALs) targeting B cells with PLGA (RAPA), the administration to K/BxN mice after disease onset could delay and in a few cases reverse disease progression, demonstrating the potential for studying treatment in a setting of ongoing disease . Future studies will be aimed at evaluation of this hybrid NP approach to suppress ongoing autoimmune responses.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, while investigating treatment of the K/BxN model of rheumatoid arthritis caused by reaction to the autoantigen glucose-6-phospate isomerase (GPI), Srivastava et al combined PLGA-RAPA NPs with Siglec-tolerizing antigenic liposomes (STALs). STALs had been previously developed to induce antigen-specific tolerance in B cells through a surface display of both the antigen and a glycan ligand for the inhibitory co-receptor CD22/Siglec-2 (CD22L) on liposomal nanoparticles (LPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation